Usefulness of the angiographic anatomy of the vein of marshall for ablation procedures for persistant atrial fibrillation. (24th May 2021) - Pastorcici, A; Andronache, M; Blendea, D; Massoulie, G; Dauphin, C; Boudias, A; Catalan, PA; Jean, F; Costea, A; Escalier, R; Mihai, PA; Rosu, R; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Ethanol Infusion in the Vein of Marshall (EIVOM) was recently proposed as an efficient adjunctive technique for obtaining mitral isthmus block during catheter ablation for persistent atrial fibrillation.  Purpose: Given these considerations the objective of this research was to delineate the angiographic anatomy of the Vein of Marshall (VOM).  Methods: Fluoroscopy images were obtained retrospectively in 124 patients with persistent atrial fibrillation who underwent coronary sinus angiography for EIVOM (96 patients) or cardiac resynchronization implant (18 patients). The measurements were performed using Osirix DICOM reader using the known diameter of the angiographic catheter for calibration. The distance between the ostium of the coronary sinus (CS) and the ostium of the VOM was measured in the anteroposterior view. Additionally, the angle at which the ostium of VOM opens in the CS was obtained.  Results: The diameter of the VOM ostium was 1.8 ± 0.6mm. The length of the VOM was 18.6 ± 9.1mm. The distancebetween the CS ostium and VOM ostium was as follows: less than 10mm for 1 patient (1%), between 11-20mm for 10 patients (10.41%), between 21-30mm for 38 patients (39.58%), 31-40mm for 31 patients (32.29%), between 41-50mm for 15 patients (15.62%) and >50mm for 1 patients (1%) (53mm).  The average takeoff angleof the VOM from the CS between the main branch of the VOM and the CS was measured at 140 degrees (range 90-175 degrees). No correlation could be made between the takeoff angle and the distance between CS ostium and VOM ostium.  In the group of patients undergoing cardiac resynchronization the takeoff angle from the CS was 153°±17° and it correlated significantly with the left ventricular systolic diameter and the left ventricular ejection fraction determined by echocardiography(r = 0.52; p = 0.008 and respectively r = 0.50; p = 0.009). Conclusions: Understanding the anatomy of the Vein of Marshall (VOM) is crucial in helping operators efficiently exploit the therapeutic potential of ethanol injection after accurate localization of such an important branch of the left atrial venous system.